Automated Acceptance Testing Tool For Requirements Validation - Nor Aiza, Moketar (2013)
Requirements validation is an important process that determine the client-stakeholders’ needs and expectation of a product are sufficiently correct and complete. Various requirements validation techniques such as requirements review, prototyping, model-based and testing-based requirements validation can help to evaluate the correctness and quality of requirements. Yet, most of these techniques are tedious, expensive and time consuming. As a result, most project participants sometimes are reluctant to invest time and effort in the requirements validation process. Moreover, there is also lack of tool support that promotes the effective collaboration among client-stakeholders in the process. Motivated from these conditions, we have developed a lightweight approach for requirements validation with automated acceptance testing tool. We have evaluated the tool’s usability via substantial usability study, expert review and comparative studies. The results were positive and demonstrate that our tool is able to facilitate the requirements validation process, and establish client-stakeholders collaboration in order to get the right requirements at the earlier stage of software development project.